Peran masyarakat untuk melakukan rekontruksi pasca bencana gunung meletus - Aisah, Aas Siti (Maliki Interdisciplinary Journal, 2024)
Natural disasters such as volcanic eruptions can cause significant damage to infrastructure, the environment, and the lives of the surrounding community. The post- disaster reconstruction process is very important to restore normal life and repair the impacts caused. The role of the community in post-disaster reconstruction is vital, both in social, economic, and environmental aspects. Local communities have in-depth knowledge of the conditions of their area, so they can play an active role in disaster management and reconstruction. In addition, community involvement in the planning and implementation of reconstruction can accelerate recovery and strengthen community resilience. Programs such as skills training, providing logistical assistance, and rebuilding houses and public facilities can involve direct community participation. Community involvement also increases a sense of ownership and awareness of the importance of maintaining environmental sustainability. Communities involved in the reconstruction process not only help improve physical conditions, but also support the psychosocial recovery process. Therefore, post-volcanic eruption reconstruction efforts must involve the community as a whole so that recovery can run effectively and sustainably.